Dystocia due to Schistosomus reflexus monster with ectopic viscera in a cow - BHADWAL, M S; SHARMA, UTSAV; KUMAR, SUDARSHAN (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to Schistosomus rejlexus monster with ectopic viscera has been studied in a cow in the present study.
Keywords: Dystocia, monster; cow